Effects of melatonin ingestion on physical performance and biochemical responses following exhaustive running exercise in soccer players - Farjallah, Mohamed; Graja, Ahmed; Mahmoud, Lobna; Ghattassi, Kais; Boudaya, Mariem; Driss, Tarak; Jamoussi, Kamel; Sahnoun, Zouheir; Souissi, Nizar; Hammouda, Omar (Biology of Sport, 2022)
Antioxidant supplementation has become a common practice among athletes to boost sport achievement. Likewise, melatonin (MEL) has been ingested as an ergogenic aid to improve physical performance. To date, no study has checked whether the multiple beneficial effects of MEL have an outcome during a maximum running exercise until exhaustion. Therefore, the present study aimed to evaluate the effect of MEL ingestion on physical performance and biochemical responses (i.e., oxidative stress) during exhaustive exercise. In a double blind randomized study, thirteen professional soccer players [age: 17.5 ± 0.8 years, body mass: 70.3 ± 3.9 kg, body height: 1.80 ± 0.08 m; maximal aerobic speed (MAS): 16.85 ± 0.63 km/h; mean ± standard deviation], members of a first league squad, performed a running exercise until exhaustion at 100% of MAS, after either MEL or placebo ingestion. Physical performance was assessed, and blood samples were obtained at rest and following the exercise. Compared to placebo, MEL intake prevented the increase in oxidative stress markers (i.e., malondialdehyde), alleviated the alteration of antioxidant status (i.e., glutathione peroxidase, uric acid and total bilirubin) and decreased post‑exercise biomarkers of muscle damage (i.e., creatine kinase and lactate dehydrogenase) (p 0.05). In conclusion, acute MEL intake before a maximal running exercise protected athletes from oxidative stress and cellular damage but without an effect on physical performance.